Investigations on the Sheet Bending Process with Elastic Tools - Geiger, Manfred; Engel, U; Vom Ende, A (Journal of Materials Processing Technology, 1991)
The forming process investigated in this study is the bending of U-shaped parts with a rigid punch and an elastic die. The methods of the finite element approach used for the process simulation are described. One of the most important input data for such an analysis is the material characterization especially the description of the rubber-like behavior of the die. The experimental and theoretical procedures to determine the material constants are presented. The process simulation is performed for three sheet materials and different values of sheet thickness and die hardness. In comparison with some experimental results it is shown that the FEM-approach is suitable to simulate the characteristic features of the whole process such as e.g. the dependence of bend angle on material and thickness of the sheet. Furthermore the observed curvature of the bent part can be understood in terms of the calculated stress distributions on the interfaces between punch and sheet, and sheet and die respectively. The process force resulting from simulation can be taken as an upper bound. Thus, the methods discussed in this study are suited to improve the understanding of the process and to assist the engineer in designing a particular bending operation. © 1991.
LFT Import::2019-07-15 (238)